Sleeve gastrectomy reveals the plasticity of the human gastric epithelium - Amit Elad; Botros Moalem; Dana Sender; Aya Bardugo; Ki-Suk Kim; Yhara Arad; Haya Benhayon; Ayelet Gal Etzyoni; Nehemia Greenstein; Aviv Halfon; Sarah Knapp; Michelle Malis; et al. (Nature Communications)
Abstract Gastrin is secreted following a rise in gastric pH, leading to gastric acid secretion. Sleeve gastrectomy (SG), a bariatric surgery where 80% of the gastric corpus is excised, presents a challenge for gastric pH homeostasis. Using histology, and single-cell RNA sequencing of the gastric epithelium in 12 women, we observed that SG is associated with an increase in a sub-population of acid-secreting parietal cells that overexpress respiratory enzymes and an increase in histamine-secreting enterochromaffin-like cells (ECLs). ECLs of SG-operated patients overexpressed genes coding for biosynthesis of neuropeptides and serotonin. Mathematical modeling showed that pH homeostasis by gastrin is analogous to non-linear proportional and integral control, that drives adaptation of the epithelium to acid-secretion demand. Quantitative model predictions were validated in patients. The results demonstrate human gastric epithelium remodeling following SG at the molecular and cellular levels, and more generally how trophic hormones enable robust adaptation of tissue function to meet physiological demand.